2017
DOI: 10.1021/jacs.6b13212
|View full text |Cite
|
Sign up to set email alerts
|

Heptacene: Characterization in Solution, in the Solid State, and in Films

Abstract: Acenes comprise an important class of organic semiconducting materials. As graphene nanoribbons of ultimate width, they are valuable atom-precise model systems for studying the properties of this form of nanoscale carbon materials. Heptacene is the smallest member of the acene series that could only be studied under matrix isolation conditions. Its existence in bulk had never been positively confirmed, despite efforts dating back more than 70 years. We report that the reduction of 7,16-heptacenequinone produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 73 publications
8
129
1
Order By: Relevance
“…Keeping 2 in a glove‐box for six weeks did not lead to any significant change in the spectrum. This is in contrast to results reported for thermally prepared heptacene, which progressively dimerised to diheptacene . It is proposed that the packing of our precursor 7 does not favour the dimerisation of heptacene 2 in the solid state.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Keeping 2 in a glove‐box for six weeks did not lead to any significant change in the spectrum. This is in contrast to results reported for thermally prepared heptacene, which progressively dimerised to diheptacene . It is proposed that the packing of our precursor 7 does not favour the dimerisation of heptacene 2 in the solid state.…”
Section: Resultscontrasting
confidence: 99%
“…Given the low solubility of 7 , it was not possible to spin‐cast this compound to obtain layers of sufficient thickness for solid‐state UV/Vis spectroscopy. However, optical absorption spectra of thin films of heptacene 2 were obtained recently by H. F. Bettinger by sublimation on sapphire at low temperature (16 K) . It was shown that annealing the films to higher temperatures resulted in a decrease of the poorly resolved p‐bands.…”
Section: Resultsmentioning
confidence: 99%
“…The larger acenes (>tetracene), first described by Clar, are important semiconductors, yet sensitive materials. As a consequence, only unsubstituted pentacene has found widespread application in organic electronics, whereby unsubstituted heptacene even though prepared by Bettinger, is too sensitive to be useful for applications . Much later, Anthony et al.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] The trend of vanishing ST splitting with growing acene length indicates the formation of polyradical structures with high chemical instability. [6][7][8][9] Thus, the availability of longer acene chains is quite limited and remains a great challenge for experimental research, 10 although recent progress in the synthesis techniques provided oligomers as large as octacene or nonacene under special conditions. 11 An efficient strategy for tailoring the electronic, magnetic and physico-chemical properties of graphene-related materials relies on the controlled introduction of substitutional defects (chemical doping).…”
Section: Introductionmentioning
confidence: 99%